Commentary to Quality Improvement Case Series: Loss of Fixation of a Type IV Supracondylar Humerus Fracture Treated with Three Divergent Lateral Pins: Quality Improvement Case Series - Jennifer M. Bauer; Steven Frick; Christine A. Ho; Kenneth David Illingworth; David Skaggs (Journal of the Pediatric Orthopaedic Society of North America, 2023)
In this manuscript, invited experts opine on the causes and potential interventions to prevent loss of fixation in supracondylar humerus fractures treated with all lateral entry percutaneous pin fixation. Experts provide tips on pin construct, technical placement, and strategies to assess stability in the operating room in hopes of reducing malunion due to loss of fixation.